Analytical Method Development And Validation of Dutasteride and Tamsulosin Hcl in Combination And Its Stress Degradation Studies - Raja Sundararajan,; Christopher Vasanth Kumar,; Jayaveera, (IJPAR JOURNAL, 2013)
Asimple,specific, sensitive,precise and reproducible Reverse Phase High Performance liquid Chromatography method has been developed for simultaneous estimation of Dutasteride and Tamsulosin Hcl. Dutasteride and Tamsulosin is Anti-hyperplasia and Anti-hypertensive drug.The determinationwas carried out byusingsymmetryC- 18columnwith Methanol:0.1M Monobasic potassiumdihydrogenphosphate buffer(75:25) Adjusted the pH to 2.5 with Ortho phosporic acid as the mobile phase and with the detection wavelength of274 nmrespectively.The flow rate is 0.7 ml/min.TheRetentiontime of Dutasteride,Tamsulosin Hcl was 2.218 minand 6.599 min respectively.Linearityforthe Dutasteride and Tamsulosin Hcl were found inthe rangeof 25-75µgmand 20-60µgm respectively.The limitof quantificationforbothdrugs wasfound to be30,24µg respectively.The recoveries of Tamsulosin and Dutasteride were found to be inthe range of 99.81-99.90 %and98.00-102.00%, respectively. The proposed methodwas validated suitablyand canbeused forroutine analysis. The degradation studies indicated Dutasteride andTamsulosin Hcl to besusceptible to neutralhydrolysis, while Dutasteride and Tamsulosin Hcl showed degradation inacid, H2O2,photolytic and inpresenceof UV radiation.The degradation productsof Dutasteride andTamsulosin Hcl inacidic and photolytic conditions were well resolved from the pure drugwithsignificant differences in the irretention time values. This method can be successfully employed forsimultaneous quantitative analysis of Dutasteride and Tamsulosin Hcl in formulations.